Legal analytics : the future of analytics in law - Malik, Namita Singh; Gromova, Elizaveta A; Gupta, Smita (Law teacher); Balusamy, Balamurugan (Boca Raton, FL : Chapman & Hall/CRC Press, 2023)
"Legal Analytics: The Future of Analytics in Law navigates the crisscrossing of intelligent technology and legal field in building up new landscape of transformation. Legal automation navigation is multidimensional wherein it intends to construct streamline communication, approval and management of legal task. Evolving environment of technology has emphasized need for better automations in legal field from time to time. Although legal scholars took long to embrace Information revolution of legal field"--
Artificial intelligence, automation & legal system / Disha Pandey & Namita S Malik -- Moving one step further : the integration of AI-based mechanisms into the Indian judicial system / Harsh Mahaseth and Saumya Pandey -- Using AI to address criminal justice needs problems & perspective / Niteesh Kumar Upadhyay & Snizhana Romashkin -- Artificial Intelligence inroads into Indian judicial system / Santhi Narayanan, Monica Agarwal & Swati Bansal -- The role of language prediction models in contractual interpretation : the challenges and future prospects of GPT-3 / Malcolm Katrak -- The impact of new technologies on taking evidence in civil court procedures -- is there a need for a conceptual change? / Tjaša Ivanc and Cocou Marius Mensah -- Legal analytics on the role of intellectual property and digital health system in overcoming public health emergency / Ranti Fauza Mayana, Ahmad Ramli and Tisni Santika -- Automation in labour sector and its effects and challenges on jobs creation : an analytical study / Jagdish Khobragade and Simran Bais -- Water scarcity : a global threat to access human right to clean water / Anuja Mishra and David W. Tushau -- The development of transportation sector in the ages of automation / Maria A. Bazhina -- Big data analytics : the new surveillance discretion for criminal justice system / Swati Kaushal & Chandrika Singh -- The use of inclusive digital technologies to improve access to justice / Sergey V. Zuev, Oksana V. Ovchinnikova, Vera A Zadorozhnaia and Tatyana P. Pestova -- The use of digital technology for enhancing proof in forensic document examination / Pavlos Kipouras -- Legal analysis in forensic investigation / Galina Rusman and Julia Morozova -- Data biases and predictive policing system in New Delhi / Baidya Nath Mukherjee and Bhupinder Singh -- How far data mining is legal! / Jayanta Ghosh and Vijoy Kumar Sinha -- Peaceful neo-Luddism : how the employee and the employer get on a digital diet? / Ofman Elena and Dulatova Natalya -- International Child Sexual Exploitation (ICSE) Database to fight child sexual abuse & artificial intelligence : challenges / Sayan Das & Paramita Chaudhary -- EU and American Charter on use of Artificial Intelligence in judicial process : model charter for India? / Taruna Jakhar and Surya Saxena.
OCLC-licensed vendor bibliographic record.
Keywords: Technology and law; Law -- Statistical methods; Quantitative research; Data mining in law enforcement; COMPUTERS / General; COMPUTERS / Computer Engineering; COMPUTERS / Database Management / Data Mining